ANALISIS FAKTOR-FAKTOR PEMBENTUK KINERJA (CAMELS) PADA PERBANKAN INDONESIA - Defrio, Mayco; Meiranto, Wahyu (Diponegoro Journal of Accounting, 2013)
ABSTRACTThe aims of this study is to determine the major factors that form the performance of the banks in Indonesia based on the CAMELS ratios. The population in this study are all banking companies listed on the Stock Exchange in 2007-2011. The sampling method used in this study was purposive sampling method with the criteria is listed for 5 years and have no delisted during the period.The total number of samples in this study were 145 research samples. However, there were 10 samples were classified as outliers and should be abolished and the number of samples become 135 samples. Company data used for this study is financial ratio that according to CAMELS ratio, consisting of PR, RAR, CAR and DRR as Capital aspects, RORA, AUR, APB and NPL as Assets aspects, LEV, CDR, SPRD, and DEBT as Management aspects, GPM, PM, ROE, ROTA, ROA, GOTA, NPM, NIM, and BOPO as Earning aspect, CASH, QUICK, LDR and ALR as Liquidity aspects, and IER as Sensitivity aspect. Techniques of analysis in this study is using factor analysis.The analysis showed that from 26 ratio, there are 25 significant ratio as forming the ratio of bank performance, and 18 of them are the permanent factors that forming the banks performance. That eighteen ratio is PR, CAR, RAR, DRR, APB, RORA, LEV, ROE, NIM, ROA, ROA, NPM, PM, GPM, ALR, CASH, QUICK, and IER